ALTERED HRT AND ABPM IN MENOPAUSAL WOMAN. (June 2018) - Stojanovic, M.; Ivovic, M.; Tancic, M.; Miletic, M.; Marina, L.; Arizanovic, Z.; Vujovic, S.; Stojkovic, M.; Beleslin, B.; Ciric, J.; Zarkovic, M.; Stojanov, V.; et al.
Abstract : Objective: A 49-year-old female, presents with a complaint of "haven't sleep well for years". For the last three years, she noticed higher BP (blood pressure) despite taking beta blocker (BB). She also noticed that some nights she wakes up sweating. She reports being more tired and with difficulty concentrating at work. MEDICAL HISTORY Hypertension. Tobacco: smoking 8 cigarettes/day for 26 years. EtOH: 2–3 glasses of wine/week. Last menstrual period 2 years ago. MEDICATION BB once/day for hypertension. PSYCHIATRIC HISTORY No. SOCIAL HISTORY Lives with a supportive husband. No pets. FAMILY HISTORY Mother 76 y.o. with history of hypertension. Design and method: PHYSICAL EXAM Height = 172 Weight = 63. Ambulatory blood pressure monitoring (Meditech ABPM05) find mean daytime 138/87 mmHg P 76/min. Mean night-time 122/73 mmHg P 62/min. LABORATORY FSH = 44 LH = 34 IU/L Estrogen = 40 pmol/L. Results: CLINICAL COURSE Trisequens (estradiol-norethisteron) was recommend to alleviate her menopause-related symptoms. Patient developed increased dysphoria during the second month of treatement. After three months Trisequens was discontinued. At the time the Trisequens was discontinued, ABPM was performed for a second time and find slightly lower blood pressure values. Mean daytime 137/86 mmHg P 76/min. Mean night-time 120/72 mmHg P 62/min. NEXT TRIAL includes estradiol and drospirenone combined therapy (Angelique). FOLLOW-UP After six months on Angelique she noticed significant improvement of her vasomotor symptoms and her sleeping pattern. ABPM was performed yet again and find significantly lower BP values when compared with the first ABPM done before she starts taking Trisequens. Mean daytime 133/82 mmHg P 76/min. Mean night-time 116/66 mmHg P 58/min. Conclusions: When adequate hormone replacement therapy is prescribed, ambulatory blood pressure monitoring cofirm good regulation of blood pressure.